ANALISIS PENGARUH CUSTOMER SATISFACTION TERHADAP E-SERVICE QUALITY BERDASARKAN E-CUSTOMER LOYALTY PADA WEBSITE TOKOPEDIA - Diansyah, Risnal; Arribe, Edo; Maula Zhakiyah, Annisa (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2021)
Tokopedia is an online buying and selling website that is safe, easy and convenient. In its services, there are still customer complaints about the quality of e-commerce services such as old delivery of goods, then the results of the goods sent do not match the criteria described on the website, then sometimes it is difficult to confirm problems about the goods purchased, and user security problems. Therefore, to overcome this problem, it is necessary to measure the quality of e-commerce services using the e-service method which focuses on six dimensions, namely Reliability, Responsiveness, Privacy / security, Information quality. / benefit (benefits / quality of information), Ease of use / usability (ease of use / usability) and Web design (site design). This study aims to determine the Analysis of the Influence of Customer Satisfaction on E-Service Quality Based on E-Customer Loyalty in Tokopedia Users. And knowing which variables get recommendations for improvement. In this study, the samples used were students of the Muhammadiyah Riau University who used Tokopedia e-commerce. Data obtained by conducting interviews, literature study and distributing questionnaires about the effect of Customer Satisfaction based on the E-servqual method to customers using Tokopedia e-commerce. Simultaneous test results (Test F) as a whole can be seen that the value of F count 132.557> F table 1.90, so it can be concluded that H1 is accepted which means there is a variable influence, namely E-Servqual (X1) and Customer Satisfaction (X2) the effect simultaneously (simultaneously) on the E-Customer Loyalty variable (Y)